An investigation of the regional expression of the vernacular architecture and cultural landscape in the Sandveld - Thomas, Guy (Department of Archaeology, 2016)
Much of the work undertaken in the field of Vernacular Architecture on the West Coast of South Africa has focused on the Verlorenvlei settlement. The buildings of this small settlement have come to define the Vernacular Architecture of the Sandveld. The Sandveld, however, is a relatively poorly understood region in terms of historical research, particularly in the 19th century, but forms an important link between events in the Cape and events on the Northern Frontier in the late 18th and 19th Century. The purpose of this study is to explore, modify and expand the characteristics of Sandveld Vernacular Architecture and build on the empirical and theoretical work done at Verlorenvlei and elsewhere through increasing the sample of buildings recorded. Additionally, the study seeks to pay attention to specific historical and biophysical contexts and considers the development of the vernacular landscape at three analytical scales, a broad, macro-scale, a midscale, and the detailed micro-scale. To do this I have drawn on multiple strands of evidence in both the documentary and archaeological record. These multiple strands of evidence contribute to an understanding of the Vernacular Architecture of the Sandveld that confronts variability that defies a singular definition of a Sandveld Vernacular.